Isolation of Caffeine from Carbonated Beverages - Amir Hassan; Muhammad Ashfaq; Ali Khan; Muhammad Shakeel Khan (Journal of Tropical Pharmacy and Chemistry, 2020)
The work presented on the isolation of naturally occurring alkaloid from carbonated beverages. The extensive presence of caffeine in different plants plays an important role in the long-standing acceptance of caffeine-containing products. Caffeine (3,7-dihydro-1, 3,7-trimethyl-1H-purine-2,6-dione or 1,3,7-trimethylxanthine) is an alkaloid belongs to Methylxanthine family. Liquid-liquid extraction methods were used in the assay of research work. Chloroform was taken as extracting solvent. Solid residue of caffeine was recrystallized from 95% ethanol using 5ml/gram (5ml per gram). It is declared to raise caffeine, effects a number of different drugs include Paracetamol, Benzodiazepines and Aspirin and amount of plasma free Fatty acids increases. While inform that in regular sleeping interaction caffeine take place and raise the absorption of certain drugs. Changes in drug metabolizing enzymes, acts as an agent in a microsomal system of the body. The highest amount of caffeine dry crystal is extracted in sting sample while the 7up sample is free from caffeine.